A steep coronal graft bending angle is associated with bone tunnel enlargement of the posterolateral bundle after anterior cruciate ligament reconstruction. (11th December 2019) - Yanagisawa, Shinya; Kimura, Masashi; Hagiwara, Keiichi; Ogoshi, Atsuko; Yoneyama, Tomotaka; Omae, Hiroaki; Miyamoto, Ryosuke; Chikuda, Hirotaka
Purpose: The correlation between the graft bending angle (GBA) of the anteromedial bundle and posterolateral bundle after anterior cruciate ligament reconstruction (ACLR) and postoperative tunnel enlargement was evaluated. Methods: Two hundred fifty-eight patients (137 males, 121 females; mean age 27.3 years) who had undergone double-bundle ACLR were included. Computed tomographic scans of the operated knee were obtained at 2 weeks and 6 months postoperatively. The area of the tunnel aperture for femoral anteromedial tunnel (FAMT) and femoral posterolateral tunnel (FPLT) was measured; the area at 2 weeks after ACLR was subtracted from the area at 6 months after ACLR and then divided by the area at 2 weeks after ACLR. The femoral tunnel angles were obtained with Cobb angle measurements. The femoral tunnel angle in the coronal plane was measured relative to the tibial plateau (coronal GBA). On the median value, the patients were divided into two groups in each of FAMT and FPLT; those with a coronal GBA of FAMT of ≥27° were classified as group A, while those with a coronal GBA of <27° were classified as group B, those with a coronal GBA of FPLT of ≥23° were classified as group C, while those with a coronal GBA of<23° were classified as group D. Results: Group A included 129 knees, while group B included 129 knees. Groups A and B did not significantly differ regarding FAMT enlargement. Group C included 133 knees, while group D included 125 knees. The percentage of FPLT enlargement in group C was significantly smaller than that in group D ( p = 0.001). Conclusions: A steep coronal GBA of the FPLT after ACLR results in greater FPLT enlargement. The present findings suggest that surgeons should avoid creating a steep GBA of the FPLT in the outside-in technique.